Tactical critical thinking program on the tactical efficiency index, declarative and procedural knowledge in male soccer players: a case study - Gaviria Alzate, Samuel Jose; Valencia-Sánchez, Wilder Geovanny; Espinal, Frank Esteban; Bustamante, Jorge Luis; Arias-Arias, Elkin (Frontiers in Sports and Active Living, 2024)
IntroductionThe purpose of this study was to explore the implications of the in-field implementation of a teaching strategy that promotes critical thinking (TPCT) on tactical ability, declarative, and procedural knowledge. The TPCT is grounded in socio-constructivist theory and aims to enhance players' analytical skills through inquiry, problem-solving, and observation. By emphasizing the socio-constructivist approach, the program fosters skills such as interpretation, analysis, inference, evaluation, explanation, and self-regulation, encouraging players' active participation in questioning and collaborative problem-solving activities. The content of the program focuses on offensive tactical principles of soccer.MethodsThirteen male U-14 soccer players (mean age: 13.54 ± 1.00 years; mean soccer-federated experience: 3.92 ± 1.00 years; mean body mass: 39.44 ± 6.09 kg; mean height: 1.61 ± 0.10 m) performed a TPCT intervention strategy over 22 sessions, three times a week. Tactical ability was assessed using the Test for Performance Assessment in Team Sports (PATS), while declarative and procedural knowledge were evaluated with the Tactical Knowledge Test in Soccer (TCTOF). These assessments were administered before and after the intervention.ResultsAfter the 8-week teaching strategy, there was a significant improvement and substantial increase in the Tactical Efficiency Index (IE) [t (12) = 2.61, p < 0.05, r = 0.73], reflecting a 41% rise from the pretest (M = 0.39, SD = 0.21) to the post-test (M = 0.55, SD = 0.24). Changes in declarative knowledge were minimal, with a 0.31% increase. Similarly, procedural knowledge showed a slight increase (3.53%) that did not reach statistical significance.DiscussionThe findings suggest that integrating critical thinking into sports training could be a strategy to enhance the tactical abilities of young soccer players. While the increase in tactical ability was significant, improvements in declarative and procedural knowledge were minimal. These results highlight the potential of critical thinking-focused programs to impact tactical performance but suggest that further research is needed to explore the broader effects on other types of knowledge.